The course of gametogenesis in narrow-clawed crayfish (Astacus leptodactylus Eschscholtz, 1823) in the condition of water bodies of the Dnieper region - I. Borovyk; O. Marenkov (Ribogospodarsʹka Nauka Ukraïni, 2024)
Purpose. Detailed study of the stages of reproductive development (oogenesis and spermatogenesis) of crayfish using the example of the narrow-clawed crayfish Astacus leptodactylus Eschscholtz, 1823 in reservoirs of the Dnieper region.